Do interpersonal trust and social avoidance mediate the association between psychotic symptoms and social functioning in chronic schizophrenia patients? - Liu, Hongyang; Pan, Xinming; Huang, Xinxin; Tian, Haijia; Shao, Xueke; Wang, Dandan; Wen, Lu; Bao, Chenxi; Fang, Xinyu; Yi, Zhenghui (Frontiers in Psychiatry, 2025)
ObjectiveSchizophrenia is a complex mental disorder that significantly impacts social functioning. The present study aimed to investigate the relationship between psychotic symptoms and social functioning in individuals with chronic schizophrenia. Specifically, we examined the mediating roles of social avoidance and impaired interpersonal trust in this relationship, as these factors are most worrisome in individuals with schizophrenia.MethodsA total of 223 outpatients with chronic schizophrenia and 201 unrelated healthy controls were included. The Positive and Negative Syndrome Scale (PANSS), the Interpersonal Trust Scale (ITS), the Social Avoidance and Distress Scale (SAD), and the simplified Chinese version of the Social Disability Screening Schedule (SDSS) were used for evaluation. Mediation analysis was performed using the PROCESS macro in SPSS23.0.ResultsOur results showed that individuals with chronic schizophrenia scored significantly lower on the ITS total and two index scores but higher on the SAD total and two index scores than healthy controls. The ITS score was significantly associated with the psychotic symptoms (both PANSS total score and subscale score) and social functioning in those patients. Interestingly, we further found that interpersonal trust had a significantly mediating effect on the relationship between psychotic symptoms (including positive, negative, cognitive, excited, and depressed symptoms) and social functioning in individuals with schizophrenia.ConclusionOur preliminary findings suggest that improving interpersonal trust may be a promising approach to enhance social functioning and improve prognosis in individuals with schizophrenia. This insight underscores the importance of incorporating trust-building interventions into clinical practice, which could potentially lead to better social outcomes for patients.